1999
DOI: 10.1046/j.1365-2648.1999.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐verbal behaviour in nurse–elderly patient communication

Abstract: Non-verbal behaviour in nurse±elderly patient communicationThis study explores the occurrence of non-verbal communication in nurse± elderly patient interaction in two different care settings: home nursing and a home for the elderly. In a sample of 181 nursing encounters involving 47 nurses a study was made of videotaped nurse±patient communication. Six non-verbal behaviours were observed: patient-directed eyegaze, af®rmative head nodding, smiling, forward leaning, affective touch and instrumental touch. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 28 publications
(45 reference statements)
1
107
0
9
Order By: Relevance
“…Although, in general, they experienced some (minor) stress in advance, the majority reported that stress did not really affect their behaviour or that of the resident and that the video reflected the normal situation. Despite the obvious fact that they were being observed, the CNAs and residents adapted to the presence of the observer, as has been often reported in observational research before [35,42].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although, in general, they experienced some (minor) stress in advance, the majority reported that stress did not really affect their behaviour or that of the resident and that the video reflected the normal situation. Despite the obvious fact that they were being observed, the CNAs and residents adapted to the presence of the observer, as has been often reported in observational research before [35,42].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the research of Caris-Verhallen et al [35,47], Kerkstra et al [13] and Kruijver [48], nonverbal affective behaviours were selected that appeared to be particularly important for the establishment of the nurse-elderly relationship. The observation scheme contains the following indicators of rapport-building nonverbal communication: three nonverbal affective categories for CNAs (eye-contact, affective touch, smiling) and two nonverbal affective categories for residents (eye-contact, smiling).…”
Section: Indicators Of Nonverbal Communicationmentioning
confidence: 99%
See 3 more Smart Citations